Economic Analysis for Sustainable Management of Marine Protected Areas in Ujung Kulon National Park (UKNP) - Suparyana, Suparyana; Fauzi, Akhmad; Kusumastanto, Tridoyo; Yulianto, Gatot (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
The protection of ecosystems and natural resources continues to be a top priority for the management of the Marine Conservation Area (MCA) of Ujung Kulon National Park (UKNP). Managers haven't given management of the economic and social use issues much thought. In reality, if it is properly managed, the MCA UKNP's economic potential can contribute to raising the economic well-being of the neighbourhood. Estimating the MCA UKNP's economic value and examining its economic and financial viability are the two goals of this manuscript. Survey research is used as the research methodology, together with overall economic valuation and financial and economic feasibility study. The findings of the study are as follows: 1) The mangrove environment, which is worth IDR1,215,105,470,571, and the coral reef ecosystem, which is worth IDR1,390,406,119,529, together make up the overall economic valuation of the MCA UKNP, which is IDR2,605,511,590,100. 2) The financial and economic feasibility analysis's findings indicate that the financial NPV is 1,963,392,508,016 and the economic NPV is 1,927,390,315,754 > 0, the financial Net B/C value is 21,28 and the economic Net B/C value is 19,30 > 1.0, and the financial IRR value is 39.54 and the economic IRR is 39.43% > 20% (MARR). The analyses' findings support the MCA UKNP's declaration that its determination was practicable.